Invest in penny stocks : a guide to profitable trading - Leeds, Peter (Hoboken, N.J. : Wiley, 2011)
"Written by a recognized and well respected authority on penny stocks, Peter Leeds has a complete commitment to ethics, as well as a front-and-center admission that 95% of penny stocks are poor choices, both of which fly in the face of the industry's conventional position. Readers learn to find the 5% that pass proprietary Leeds Analysis, which empowers regular people (even first time investors) to find life-changing investments, which they can buy for small amounts and make surprisingly large returns. Using methods of fundamental analysis honed over many years, Peter Leeds discovers value in companies that others can't see. You'll learn how to look at a firm's future earnings trend, its efficiency compared to competitors, and the soundness of its financial structure. Leeds offers innovative methods of technical analysis to generate long-term investment success."--
Preface -- Experience Level Rating System (EL) -- Chapter 1: The Big Business of Penny Stocks -- Chapter 2: Getting Started in Penny Stocks -- Chapter 3: Avoid Your Rough Start -- Chapter 4: Leeds Analysis -- Chapter 5: Third Level Analysis -- Chapter 6: Fundamental Analysis -- Chapter 7: Share Structure -- Chapter 8: Technical Analysis -- Conclusion: The Way of Penny Stocks -- Acknowledgments -- Index.
Includes index.
Print version record.
Keywords: Penny stocks; Investments; Business; BUSINESS & ECONOMICS -- Investments & Securities -- Stocks; Investments; Penny stocks; Electronic books